Real Exchange Rates and the International Mobility of Capital - Anwar M. Shaikh (Levy Economics Institute of Bard College, 1999)
This paper demonstrates that the terms of trade are determined by the equalization of profit rates across international regulating capitals, for socially determined national real wages. This provides a classical/Marxian basis for the explanation of real exchange rates, based on the same principle of absolute cost advantage which rules national prices. Large international flows of direct investment are not necessary for this result, since the international mobility of financial capital is sufficient. Such a determination of the terms of trade implies that international trade will generally give rise to persistent structural trade imbalances covered by endogenously generated capital flows which will fill any existing gaps in the overall balance of payments. It also implies that devaluations will not have a lasting effect on trade balances, unless they are also attended by fundamental changes in national real wages or productivities. Finally, it implies that neither the absolute nor the relative version of the Purchasing Power Parity hypothesis (PPP) will generally hold, with the exception that the relative version of PPP will appear to hold when a country experiences a relatively high inflation rate. Such patterns are well documented, and in contrast to comparative advantage or PPP theory, the present approach implies that the existing historical record is perfectly coherent. Empirical tests of the propositions advanced in this paper have been conducted elsewhere, with good results.
Keywords: 330